Effect of surface nanocrystallization on high-cycle fatigue behavior of Ti–2Al–2.5Zr alloy tube. (May 2022) - Chen, Gang; Chu, Tianshu; Cui, Yun; Wu, Yuntao; Liu, Xiao; Lin, Qiang
Highlights: The gradient nanostructured layer was produced by deep rolling (DR) treatment on the inner wall of Ti-2Al-2.5Zr alloy tubes. DR treatment increased the tensile strength of the tubes by 12%. The fatigue limit of the DR sample was 13.5% higher than that of the as-received sample. Effects of gradient nanostructured surface layers on fatigue cracking mechanisms were clarified. Abstract: Gradient nanostructured surface (GNS) can enhance the properties of metals and alloys. Here, the effect of GNS layers on the lifetime of a Ti-based alloy were investigated. Stress-controlled high-cycle fatigue (HCF) tests were carried out to study the fatigue behavior of Ti–2Al–2.5Zr alloy tubes with different GNS layers obtained via deep rolling (DR) treatment. The fracture failure mechanism was analyzed using the quantitative tilt technique, continuous-slice method, and electron backscatter diffraction. The DR samples had lower surface roughness, an added hardening layer, and better comprehensive mechanical properties than the as-received samples. Furthermore, after 10 7 cycles of the DR treatment, the fatigue strength of the samples was enhanced from 166.5 to 189 MPa, and the initiation sites of the fatigue cracks moved from the surface to the subsurface. The facets of crack initiation along the slip system in the as-received samples were revealed. The nanocrystals and twins generated by DR treatment were considered to retard crack initiation and propagation, thus increasing HCF life.